H∞ analysis and design for delay systems with polytopic-type uncertainties - Xu, Honglei; Lai, C.; Luo, R.; Zhang, R. (Yokohama Publishers, 2016)
This paper studies the H∞ filter design problem for delay systems with polytopic-type uncertainties. A novel Lyapunov-Krasovkii-based H∞ filter design technique is developed to ensure that both the filter error dynamic system is asymptotically stable and the given H∞ performance is satisfied. In addition, based on these H∞ performance analysis results, an efficient filter is designed by using sufficient conditions expressed in form of linear matrix inequalities (LMI), which can be efficiently solved by convex optimization techniques.